Estudo da variabilidade interobservadores das medidas ultrassonográficas do diâmetro biventricular externo/ comprimento do fêmur, nos modos M e B, em fetos de gestantes isoimunizadas - Flavia Mafra Guimaraes e Silva (2010)
The maternal red-cell alloimmunization is a serious disease that still affects a large number of pregnant women in Brazil, even already existing prevention for most cases. To decrease the perinatal morbidity and mortality, the diagnosis of fetal anemia will provide appropriate treatment. Due to complications related to invasive procedures for fetal monitoring (amniocentesis and cordocentesis), noninvasive tests have been developed through studies of the pathophysiology of fetal disease. The anemic fetus presents dilatation of the cardiac chambers, which can be verified by measuring the cardiofemoral index (fetal biventricular outer dimension in diastole / femur length) increased. It is a method with proven accuracy through various works completed in CEMEFE HC / UFMG. The present study evaluates the reproducibility of the cardiofemoral index. Objective: To study the interobserver variability of ultrasonographic measurements of fetal biventricular outer dimension in diastole / femur length in M and B modes, in fetuses of pregnant isoimmunized. Patients and methods: Eighteen fetuses of sixteen isoimmunized women were followed at CEMEFE HC / UFMG by noninvasive tests, for the diagnosis of fetal anemia, in the period from July 2008 to April 2009. The measurements were performed by two observers on the same day, consecutively, which measured the fetal biventricular outer dimension in diastole by B-mode and M-mode. Only one fetal femur length, of one of the observers was used to calculate the cardiofemoral index. The ultrasound device used was SonoAce 8800 (MEDSOM ®) with a 3.5 MHz sector probe and acoustic filter of 100 Hz. Statistical methods were used to calculate the interobserver error, the analysis of agreement between methods of Bland-Atman and the index of concordance kappa. Results: One hundred sixty-eight ultrasounds measurements of fetal biventricular outer dimension in diastole were performed in the M and B modes by the two observers. Of the 56 measurements realized in commom by observer 1 and 2 in M mode, the interobserver error was the mean of 6.2% ± 5%, the Bland-Altman plot showed good agreement between measurements and through the kappa index linear, the mean value of 0.5 indicates a moderate agreement in diagnosing fetal cardiac dilatation. In mode B were 42 measurements in common, the interobserver error was the mean of 5.8% ± 7.1%, the Bland-Altman plot showed good agreement between the measures and kappa linear index value was 0.43 and indicate a moderate agreement. Conclusion: There was good agreement between the ultrasonographic measurements of fetal biventricular outer dimension in diastole / femur length, M and B modes, examiners 1 and 2, considering the analysis of agreement between methods of Bland-Altman. There is a moderate interobserver agreement in the diagnosis of fetal cardiac chambers dilatation, considering the kappa index of concordance.